2019
DOI: 10.1111/ene.14009
|View full text |Cite
|
Sign up to set email alerts
|

Neuromelanin or DaT‐SPECT: which is the better marker for discriminating advanced Parkinson's disease?

Abstract: Background and purposeWhether the neuromelanin‐positive substantia nigra pars compacta area (NM‐SNc) on neuromelanin magnetic resonance imaging (NM‐MRI) and the specific binding ratio (SBR) on 123I‐N‐v‐fluoropropyl‐2b‐carbomethoxy3b‐(4‐iodophenyl)nortropane single photon emission computed tomography (DaT‐SPECT) can be correlated with motor fluctuations (MFs) in advanced Parkinson's disease (PD) was investigated.MethodsThirty‐five PD patients (60 ± 13 years) and 23 healthy individuals as controls (59 ± 19 years… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
23
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(29 citation statements)
references
References 23 publications
4
23
0
2
Order By: Relevance
“…Given that a recent study showed that the signal intensity in neuromelanin‐sensitive MRI (NM‐MRI) is correlated with NM concentration (Cassidy et al, 2019), an analysis using NM‐MRI may help determine which area is most impacted in early‐stage IPD. In previous studies, in order to determine abnormality in the SNpc, a contrast ratio (CR) was measured in the two or three subdivisions of the SNpc (Fabbri et al, 2017; Ohtsuka et al, 2014; Prasad et al, 2018; Wang et al, 2018; Xiang et al, 2017), or a whole or regional volume of the SN was calculated using a specific threshold (Castellanos et al, 2015; Isaias et al, 2016; Kashihara, Shinya, & Higaki, 2011; Kuya et al, 2018; Le Berre et al, 2019; Matsusue et al, 2019; Ogisu et al, 2013; Okuzumi et al, 2019; Pyatigorskaya et al, 2018; Reimao, Pita Lobo, Neutel, Correia Guedes, et al, 2015; Reimao, Pita Lobo, Neutel, Guedes, et al, 2015; Schwarz et al, 2011; Schwarz, Xing, Tomar, Bajaj, & Auer, 2017; Takahashi et al, 2018; Taniguchi et al, 2018; Vitali et al, 2020; Zupan, Suput, Pirtosek, & Vovk, 2019), and the values were compared between IPD patients and healthy subjects. These results failed to specify the most affected region of the SNpc.…”
Section: Introductionmentioning
confidence: 99%
“…Given that a recent study showed that the signal intensity in neuromelanin‐sensitive MRI (NM‐MRI) is correlated with NM concentration (Cassidy et al, 2019), an analysis using NM‐MRI may help determine which area is most impacted in early‐stage IPD. In previous studies, in order to determine abnormality in the SNpc, a contrast ratio (CR) was measured in the two or three subdivisions of the SNpc (Fabbri et al, 2017; Ohtsuka et al, 2014; Prasad et al, 2018; Wang et al, 2018; Xiang et al, 2017), or a whole or regional volume of the SN was calculated using a specific threshold (Castellanos et al, 2015; Isaias et al, 2016; Kashihara, Shinya, & Higaki, 2011; Kuya et al, 2018; Le Berre et al, 2019; Matsusue et al, 2019; Ogisu et al, 2013; Okuzumi et al, 2019; Pyatigorskaya et al, 2018; Reimao, Pita Lobo, Neutel, Correia Guedes, et al, 2015; Reimao, Pita Lobo, Neutel, Guedes, et al, 2015; Schwarz et al, 2011; Schwarz, Xing, Tomar, Bajaj, & Auer, 2017; Takahashi et al, 2018; Taniguchi et al, 2018; Vitali et al, 2020; Zupan, Suput, Pirtosek, & Vovk, 2019), and the values were compared between IPD patients and healthy subjects. These results failed to specify the most affected region of the SNpc.…”
Section: Introductionmentioning
confidence: 99%
“…Using manual delineation of the SN, studies reported [50][51][52] that the SN size correlated with DaT-SPECT results in PD. Okuzumi et al [50] found that several clinical tools commonly used to assess the severity of PD correlated better with SN size but not as well with DaT-SPECT results. However, manual segmentation methods tend to be subjective, and volumetric analysis is unacceptably time-consuming.…”
Section: Discussionmentioning
confidence: 99%
“…However, we endeavored to provide alternative eligible reference standard for the proper decision of the nigrosome-1 status by addressing clinical diagnosis, and, more importantly, by assessing the results from 123I-FP-CIT SPECT. Moreover, Okuzumi et al [35] suggested that neuromelanin-imaging is a better marker for discriminating advanced PD than SPECT, but in early stage of the disease, SPECT could be superior to neuromelanin-imaging. Therefore, in our study which included many de novo PD patients in their early stage of the disease, 123 I-FP-CIT SPECT could act as an effective and decisive proof for the true nigrosome-1 status.…”
Section: I-fp-cit Spect Is a Proven Modality With A High Diagnostic Accuracymentioning
confidence: 99%